The application of islamic values in the health services: a nurse perspective - Qowi, Nurul Hikmatul; Harmiardillah, Sylvi; Lestari, Trijati Puspita (University of Muhammadiyah Malang, 2023)
Introduction: Public awareness of the need to practice Islam in all aspects of life is increasing, including in health services. High motivation of the hospital in implementing Islamic health services has not been followed by clinics which are under Muhammadiyah charity businesses. Objectives: This study aimed to describe Islamic values at the Muhammadiyah Clinics in Lamongan Regency. Methods: The researchers used a descriptive method with a survey approach. All nurses at eleven Muhammadiyah Clinics in Lamongan Regency were selected to be the sample using purposive sampling. Seventy-one health workers filled out a 21-item-questionnaire on the application of Islamic values which had been modified by the researchers. The data were analysed by using descriptive analysis. Results: The application of Islamic values by health workers in the Muhammadiyah clinics was categorized poor (42.3%), and good (35.2%). The analysis of instrument items showed a low mean value in guiding prayer activities before surgery (1.67), reminding the spiritual guidance officers to make visits to the room (1.69), and giving prayer guidance to patients by the spiritual guidance officers (1.79). A high mean value was obtained for having prayer facilities/mosque (4.00), employees who prayed 5 times a day (3.96), and employees who recited bismillah for every medication and medical procedure (3.94). Conclusions: The role of the spiritual guidance officers at the clinic is very important to help fulfil spiritual needs and increase patient comfort. Clinic facilities that support the formation of an Islamic atmosphere need to be maintained, including monitoring employee attitudes and behaviour in daily life in accordance with Islamic teachings. The application of Islamic values can be an attraction for people in choosing a place to get health services.